The Impact of National Cultural Symbols on Students’ Creativity in Visual Arts Education - Raxmonova Mahliyo Zoir qizi, (O‘RTA OSIYODA IJTIMOIY VA GUMANITAR TADQIQOTLAR, 2025)
Abstract: This article examines the role of national cultural symbols in visual arts education. It explores how incorporating traditional motifs, colors, and symbolic designs in lessons helps students develop creativity, aesthetic perception, and cultural understanding. The paper also presents pedagogical strategies for effectively integrating national symbols into contemporary art education practices.